2021
DOI: 10.3390/ijerph182211819
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Association between Emotional Intelligence and Self-Control among University Student-Athletes

Abstract: The purpose of this study was to reveal the peculiarities of undergraduate studies university student-athletes’ emotional intelligence and self-control indicators, and the role of gender as a predictor in the association between emotional intelligence and self-control. The study included students regularly involved in training at least three times a week. The sample consisted of 1395 student athletes from Lithuanian universities, among them 59.2% female and 40.8% male. For measurement, the SSRI inventory and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(93 reference statements)
1
2
0
Order By: Relevance
“…In our sample of competitive athletes, women reported lower self-control than men. This aligns with previous athlete studies conducted pre- and mid-pandemic ( Dumciene and Sipaviciene, 2021 ; Martínez-Patiño et al, 2021 ). However, women reporting lower self-control may in fact reflect gender differences in beliefs, rather than the neurocognitive capacity, of behavioral inhibition ( De Ridder et al, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…In our sample of competitive athletes, women reported lower self-control than men. This aligns with previous athlete studies conducted pre- and mid-pandemic ( Dumciene and Sipaviciene, 2021 ; Martínez-Patiño et al, 2021 ). However, women reporting lower self-control may in fact reflect gender differences in beliefs, rather than the neurocognitive capacity, of behavioral inhibition ( De Ridder et al, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…They can better deliver on promises and achieve better results at work. Better self-control skills could likely be associated with higher achievement in certain areas of activity (Dumciene & Sipaviciene, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Emotional intelligence plays an important role in adapting people to the demands of the social environment, helping university students to overcome stressful situations [ 34 , 36 , 38 ]. Although several previous studies about gender differences showed that females seem to recognize and deal with emotions better than males [ 22 , 39 , 40 , 65 , 66 , 67 ], recent studies during the COVID-19 pandemic reveal that males scored significantly higher than females on several emotional intelligence such as emotion management and emotional stability [ 23 , 41 , 68 ].…”
Section: Discussionmentioning
confidence: 99%